Kane and abel - Archer, Jeffrey (London : Harper Collins Publishers Ltd, 1980)
Little e fills his box with eggs, elves, and other things beginning with the short letter "e".
Keywords: Capitalists and financiers -- United States -- Fiction; Peasants -- Poland -- Fiction; Capitalists and financiers